Komposisi Vocal Konvensional “Rintihan Rindu” - Apriliyanti, Nazva; Setiaji, Denden (Jurnal Ilmu Sosial, Humaniora dan Seni, 2025)
"Rintihan Rindu" is a conventional vocal composition that uses the human voice as its primary medium without musical instruments or lyrics. Using only one word, "haaa", this composition explores the expressive power of nonverbal vocals. To create a contemplative feel, emphasis is placed on the formation of four-voice harmony, ABA-shaped musical structure, A major tonality, and 6/4 meter. The creation is based on the composer's personal experience and reflection on the idea of simplicity, serenity, and the power of the human voice as an emotional instrument. This work demonstrates that the human voice can be a meaningful medium for conveying emotions without relying on text or musical instruments, and that the human voice can serve as an artistic alternative for the development of vocal compositions in an academic environment.